2015
DOI: 10.1038/cdd.2015.123
|View full text |Cite
|
Sign up to set email alerts
|

Functional regulation of FoxO1 in neural stem cell differentiation

Abstract: Forkhead transcription factor family O (FoxO) maintains adult stem cell reserves by supporting their long-term proliferative potential. MicroRNAs (miRs) regulate neuronal stem/progenitor cell (NSPC) proliferation and differentiation during neural development by controlling the expression of a specific set of target genes. In the neurogenic subventricular zone, FoxO1 is specifically expressed in NSPCs and is no longer detected during the transition to neuroblast stage, forming an inverse correlation with miR-9 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
72
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(79 citation statements)
references
References 49 publications
(47 reference statements)
4
72
2
Order By: Relevance
“…In normal neural progenitors, FOXO3 inhibits ASCL1-dependent neurogenesis and also restrains neurogenesis in vivo (Webb et al, 2013). Similarly, constitutively active FOXO1 inhibits while its knockdown increases neurogenic differentiation of neural progenitors (Kim, Hwang, Muller & Paik, 2015). These findings together raise the possibility that FOXOs suppress lineage commitment and such activity may help maintaining the NSC reserves throughout the lifetime.…”
Section: Neural Development and Stem Cell Maintenancementioning
confidence: 99%
“…In normal neural progenitors, FOXO3 inhibits ASCL1-dependent neurogenesis and also restrains neurogenesis in vivo (Webb et al, 2013). Similarly, constitutively active FOXO1 inhibits while its knockdown increases neurogenic differentiation of neural progenitors (Kim, Hwang, Muller & Paik, 2015). These findings together raise the possibility that FOXOs suppress lineage commitment and such activity may help maintaining the NSC reserves throughout the lifetime.…”
Section: Neural Development and Stem Cell Maintenancementioning
confidence: 99%
“…One question that arises from our results is the precise genes that are regulated by miR-9. The transcription factor FOXO1 has been identified as a target of miR-9 in haematopoietic cells and neural cells [21,35]. We found that a miR-9 mimic significantly inhibited the activity of the 3′-untranslated region of Foxo1 mRNA and FOXO1 expression in mouse liver cells (data not shown).…”
Section: Discussionmentioning
confidence: 73%
“…The transcription factor FOXO1 is a regulator of gluconeogenesis and is a target of miR-9 in haematopoietic cells and neural cells [21,35]. We investigated whether FOXO1 is required for the miR-9 inhibition of gluconeogenesis and glucose output.…”
Section: Mir-9 Suppresses Gluconeogenesis and Hpg By Directly Targetimentioning
confidence: 99%
“…The nucleotide sequence of miR‐9 is 100% identical from insects to mammals, suggesting that its functional preservation is evolutionarily important. In mammals, miR‐9 is highly expressed in neurogenic areas, and its expression is gradually increased during neuronal differentiation . Consistent with this expression pattern, miR‐9 accelerates neural differentiation at the expense of NSPC proliferation inhibition.…”
Section: Post‐transcriptional Regulatorsmentioning
confidence: 66%
“…Id2, which antagonizes neuronal differentiation, is also suppressed by miR‐9 . Recently, FoxO1 was determined to be a new molecular target of miR‐9 . Since FoxO1 cooperates with the Notch pathway to NSPC maintenance, the reduced expression of FoxO1 by miR‐9 induced cell differentiation.…”
Section: Post‐transcriptional Regulatorsmentioning
confidence: 99%